Genetic characteristics, antimicrobial susceptibility, and virulence genes distribution of Campylobacter isolated from local dual-purpose chickens in central China - Xiao, Jia; Cheng, Yiluo; Zhang, Wenting; Lu, Qin; Guo, Yunqing; Hu, Qiao; Wen, Guoyuan; Shao, Huabin; Luo, Qingping; Zhang, Tengfei (Frontiers in Cellular and Infection Microbiology, 2023)
Food-borne antibiotic-resistant Campylobacter poses a serious threat to public health. To understand the prevalence and genetic characteristics of Campylobacter in Chinese local dual-purpose (meat and eggs) chickens, the genomes of 30Campylobacter isolates, including 13 C. jejuni and 17 C. coli from Jianghan-chickens in central China, were sequenced and tested for antibiotic susceptibility. The results showed that CC-354 and CC-828 were the dominant clonal complexes of C. jejuni and C. coli, respectively, and a phylogenetic analysis showed that three unclassified multilocus sequence types of C. coli were more closely genetically related to C. jejuni than to other C. coli in this study. Of the six antibiotics tested, the highest resistance rates were to ciprofloxacin and tetracycline (100%), followed by lincomycin (63.3%), erythromycin (30.0%), amikacin (26.7%), and cefotaxime (20.0%). The antibiotic resistance rate of C. coli was higher than that of C. jejuni. The GyrA T86I mutation and 15 acquired resistance genes were detected with whole-genome sequencing (WGS). Among those, the GyrA T86I mutation and tet(O) were most prevalent (both 96.7%), followed by the blaOXA-type gene (90.0%), ant(6)-Ia (26.7%), aac(6')-aph(3'') (23.3%), erm(B) (13.3%), and other genes (3.3%). The ciprofloxacin and tetracycline resistance phenotypes correlated strongly with the GyrA T86I mutation and tet(O)/tet(L), respectively, but for other antibiotics, the correlation between genes and resistance phenotypes were weak, indicating that there may be resistance mechanisms other than the resistance genes detected in this study.Virulence gene analysis showed that several genes related to adhesion, colonization, and invasion (including cadF, porA, ciaB, and jlpA) and cytolethal distending toxin (cdtABC) were only present in C. jejuni. Overall, this study extends our knowledge of the epidemiology and antibiotic resistance of Campylobacter in local Chinese dual-purpose chickens.